Using Picture Media to Improve Reading Skills of Elementary School Students - Lestari, Della Rosty Ayu; Tiyas, Elok Yanuning; Nisa, Prama Hamza; Finorina, Finorina (research, training and philanthropy institution Natural Aceh, 2025)
Language learning plays a crucial role in the intellectual, social, and emotional development of students, as well as their success across all subjects. In the context of education in Indonesia, the subject of the Indonesian Language aims to enhance students' communication skills, both orally and in writing, while fostering a love for literary works. Reading, listening, speaking, and writing skills are integral components of the curriculum, with reading ability being a fundamental skill that elementary school students must master. The inability to read can lead to difficulties following lessons across all subjects and understanding information from various sources. This study employs Classroom Action Research (CAR) to improve the reading skills of first-grade students at SD Negeri 5 Metro Timur through visual media. The results indicate that the use of visual media significantly enhances student motivation and participation, as well as their reading abilities. In the first cycle, the average student score increased from 58% to 70%, and in the second cycle, it rose to 86.7%, with 86.7% of students meeting the Minimum Completeness Criteria (KKM). These findings demonstrate that visual media effectively improves reading skills and should be integrated into teaching strategies in elementary schools.